City size, employer concentration, and wage income inequality - Daniel Halvarsson; Martin Korpi (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2025)
This study investigates the relationship between the urban wage premium and employer concentration using Swedish full population employer-employee data. Departing from an AKM modeling framework to distinguish worker from firm specific heterogeneity - a measure of rent-sharing - we then measure the urban wage premium using differences in the estimated firm fixed effects at the level of local industries, nested within local labor markets. Our results suggest that labor market employer concentration, as calculated using the Hirschman-Herfindahl index and a leave-one-out instrumental variable design, can account for a significant share of the estimated urban wage premium (UWP). Addressing city-level wage income inequality by applying our model to different segments of the local labor market income distribution, we find that while the UWP pertains to all income segments, it is largest for top-income levels (above the 90th percentile), and within this segment employer concentration also has the largest explanatory power. Thus, while being an important explanatory factor for all percentiles of the local income distribution, a relatively lower employer concentration within larger cities, and vice versa, higher concentration within smaller cities, primarily help explain the variance of top wages within these cities/labor markets.
Keywords: D22; J31; J42; R12; 330; wage distribution; rent sharing; monopsony; linked employer-employee data; local labor markets